Maxillary Sinus Floor Augmentation with Autogenous Bone Graft Alone Compared with Alternate Grafting Materials: a Systematic Review and Meta-Analysis Focusing on Histomorphometric Outcome - Thomas Starch-Jensen; Daniel Deluiz; Niels Henrik Bruun; Eduardo Muniz Barretto Tinoco (Stilus Optimus, 2020)
Objectives: The objective of present systematic review was to test the hypothesis of no difference in histomorphometric outcome after maxillary sinus floor augmentation with autogenous bone graft alone compared with alternate grafting materials applying the lateral window technique. Material and Methods: MEDLINE (PubMed), Embase and Cochrane library search in combination with hand-search of relevant journals were conducted. Human studies published in English until the 25th of March, 2020 were included. Histomorphometric outcomes were evaluated by descriptive statistics and meta-analysis including 95% confidence interval (CI). Results: Electronic search and hand-searching resulted in 1902 entries. Sixteen randomized controlled trials with unclear risk of bias fulfilled the inclusion criteria. Descriptive statistics showed comparable or improved histomorphometric outcomes with autogenous bone graft. Meta-analysis revealed a mean difference of -7.1% (CI = -11.0 to -3.2) indicating a significant higher amount of bone after maxillary sinus floor augmentation with autogenous bone graft compared with alternate grafting materials. Subgroup analysis demonstrated a non-significantly differences of -3.7% (CI = -10.9 to 3.4), -11.5% (CI = -25.9 to 2.8), 2.2% (CI = -16.9 to 21.3), and -4.6% (CI = -14.4 to 5.2), when autogenous bone graft was compared with allogeneic bone graft, xenograft, composite grafting materials involving xenograft or synthetic biomaterial mixed with autogenous bone graft, respectively. Conclusions: Maxillary sinus floor augmentation with autogenous bone graft seems to facilitate improved histomorphometric outcomes compared with alternate grafting materials. However, the included studies were characterised by an unclear risk of bias and various methodological confounding factors. Hence, the conclusions drawn from the results of present study should be interpreted with caution.